Simulation of lower Cambrian oil and gas generation and phase evolution process in ZH1 of Tazhong area - Luo, Xinsheng; Yang, Chunlong; Zhao, Qing; Cheng, Ming; Zhang, Ke; Su, Jin; Li, Dengke (Frontiers in Earth Science, 2024)
The Lower Cambrian petroleum system in the Tarim Basin has undergone multiple periods of tectonic movements, leading to successive hydrocarbon expulsion events and adjustments. The complex process of hydrocarbon accumulation occurred under deep burial conditions, persisting at depths of nearly 6,000 m over an extended period. This has resulted in the current occurrence of various phases including light oil, condensate, and gas in the deep-ultradeep strata of the Tarim Basin. The intricacies of formation of hydrocarbon accumulations and phase evolution have posed challenges to understanding the accumulation mechanisms and enrichment patterns of the Cambrian in the Tarim Basin, consequently lowering the success rate of oil and gas exploration. Such characteristics of multi-stage accumulation and adjustment are prevalent in deep hydrocarbon systems. Therefore, based on data from Well ZH1 in the Tazhong Uplift, combined with basin simulation, Compositional kinetics model, and PVT performance simulation, this study investigates the hydrocarbon generation and phase evolution processes in the deep hydrocarbon systems of the Tazhong Uplift. The results indicate that Well ZH1 entered the hydrocarbon generation peak during the Late Ordovician, followed by secondary cracking as the predominant hydrocarbon evolution process. Hydrocarbon fluids within the Lower Cambrian reservoir transitioned into the condensate phase towards the end of the Cambrian, with increasing depth resulting in higher gas-oil ratios and a decreasing trend in viscosity and density.